Psychological distress among bariatric surgery candidates: The roles of body image and emotional eating. Issue 2 (1st February 2019) - Geller, Shulamit; Levy, Sigal; Goldzweig, Gil; Hamdan, Sami; Manor, Anat; Dahan, Shiran; Rothschild, Eyal; Stukalin, Yelena; Abu‐Abeid, Subhi
Abstract : The increased risk of psychological distress among bariatric surgery candidates may be attributed, at least in part, to body image dissatisfaction (BID). The aim of the present study was to test the hypotheses that body image could be correlated with the psychological distress variables, and that emotional eating behaviours could mediate the relationship between body image and psychological distress. A sample of consecutive participants seeking bariatric surgery (N = 169, 67% females, mean age, 41.8 years [SD = 11.46], mean body mass index 42.0 kg/m 2 [SD = 11.0]) was recruited from a university‐based bariatric centre, a week prior to scheduled surgery. Results showed that BID was positively correlated with suicidality ( r = 0.18, P < 0.05), depression ( r = 0.39, P < 0.01) and anxiety ( r = 0.20, P < 0.05). The relation between BID and depression was partially mediated by emotional eating, whereas the relation between BID and suicidality was fully mediated by emotional eating. Physicians and other health professionals who treat bariatric surgery patients should be encouraged to detect behaviours indicating emotional eating, as these could be an indicator of psychological distress resulting from poor body image.